Haemophilus parasuis Serovars Isolated from Pathological Samples in Northern Italy. Issue 2 (11th April 2012) - Luppi, A.; Bonilauri, P.; Dottori, M.; Iodice, G.; Gherpelli, Y.; Merialdi, G.; Maioli, G.; Martelli, P.
Summary From January 2007 to December 2011, a total of 106 Haemophilus parasuis strains isolated from pigs were serotyped by agar gel diffusion test (DG). Serovar 4 was the most prevalent (24.5%), followed by serovar 13 (19.8%) and serovar 5 (11.3%). Twenty‐nine strains were non‐typeable (27.3%). The strains were divided into two groups, depending on whether they were isolated from specific pathological lesions of systemic disease such as polyserositis, arthritis or meningitis (73 cases of 106) or from the lower respiratory tract of pigs suffering from bronchopneumonia (33 cases of 106). Serovars 4 and 13 had a higher prevalence in systemic infection (polyserositis) than in respiratory disease only. Pasteurella multocida (14/106), Streptococcus suis (7/106), Actinobacillus pleuropneumoniae (4/106), Bordetella bronchiseptica (3/106) and Arcanobacterium pyogenes (3/106) were isolated in association with H. parasuis.